Synthesis, structure, morphology evolution and magnetic properties of single domain strontium hexaferrite particles. (1st April 2016) - Chen, Deyang; Zeng, Dechang; Liu, Zhongwu
Abstract: Single domain strontium ferrite particles (SrFe12 O19 ) with hexagonal morphology were synthesized by conventional ceramic process. Effects of Fe/Sr mole ratio and milling time on structure, morphology and magnetic properties of the strontium ferrite particles have been systematically studied. Single phase SrFe12 O19 was successfully synthesized in a large composition range of Fe/Sr ratio (Fe/Sr = 9–11). The particle size refinement effect and the morphology change were observed with the increase of Fe/Sr ratio. It was also found that the change of Fe/Sr ratio had little effect on the magnetization curve. However, the magnetization process was significantly influenced with different milling time. The optimal magnetic properties obtained at Fe/Sr = 11 with 6 h milling are 68.2 emu g −1 and 5540 Oe for saturation magnetization ( M S ) and intrinsic coercivity ( H C ), respectively. The high performance single domain strontium hexaferrite particles obtained in this paper would greatly facilitate the application in the permanent magnet industry.